Masa Remaja sebagai Periode Kritis Perkembangan: Tantangan Pembentukan Identitas Diri di Era Digital dalam Kajian Literatur - Nurhillal Bestari; Yuliana Intan Lestari (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Adolescence is a critical developmental period characterized by the process of identity formation. At the same time, the rapid advancement of digital technology and the increasing use of social media have created both opportunities and challenges for adolescents in developing their identities. This study aims to analyze the role of social media in adolescent identity formation and to identify the factors influencing identity development in the digital era. The study employed a qualitative descriptive approach using a narrative literature review method. Data were collected through a document analysis of five national and international scientific articles selected based on relevance, publication recency, and alignment with the research topic. Data were analyzed using content analysis to identify themes, patterns, and relationships among findings reported in the reviewed literature. The results indicate that social media serves as a platform for self-exploration, identity presentation, and social validation among adolescents. Identity formation is influenced by personal, interpersonal, motivational, and affective factors, while excessive and uncontrolled social media use may contribute to social comparison, pressure to present an idealized self-image, identity confusion, and various mental health concerns. Conversely, family support, peer relationships, and adequate digital literacy function as protective factors that promote healthy identity development. This study contributes to the advancement of developmental psychology literature on adolescent identity in the digital era and highlights the importance of guidance and digital literacy enhancement in supporting the development of positive and adaptive identities among adolescents.